Democracia e liberdade: a falsa promessa do liberalismo no estado ainda-não-democrático de direito brasileiro - Bittar, Guilherme de Moraes (2021)
This research aims to carry out an analysis of the trajectory of liberalism and democracy in Brazil, observing, specifically, the governmental behavior and deportment of recent years. To this end, it intends to establish a study on the conceptions of democracy throughout history, from its ancient stage, in Athens, until its reconfiguration with the influxes of liberalism in the modern era. Still, it aims to analyze liberalism as a political theory of freedom, defining the contours of what we believe to be its main goals, such as the Rule of Law, Constitutionalism and Human Rights. Finally, the focus turns to the analysis of liberalism and democracy in Brazil, first, throughout its constitutions, and then, of the late years, in which there has been a notable reduction in the liberal-democratic process in the country, due to reiterated acts of government that undermined the still frangible Democratic Rule of Law, through attacks and threats towards civil and political freedoms and the structures of representative democracy.